Validitas Video Animasi Powtoon Kelas X SMA Berdasarkan Hasil Inventarisasi Jamur Makroskopis - Khairi Khairi; Laili Fitri Yeni; Titin Titin (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Powtoon is an software  animation video that can be accessed online, contains simple and interesting animations, and provides music facilities and can record narration. This study aims to determine the feasibility of an animated video powtoon based on the results of an inventory of macroscopic fungi found in the Sekadau Mount Protection Forest, Sambas Regency. The research instrument used is a validation sheet, which includes aspects of format, content, language, simplicity, illustrations, media quality, and attractiveness. This type of research is research and development with the Plomp model. The results showed that the validation of the animated video powtoon was carried out by five validators with a CVI (Content Validity Index) value of 0.99 which was declared feasible. Based on the validation results, it can be concluded that the animated powtoon video in the class X high school mushroom classification submaterial is declared suitable for use as a learning medium.